Blood Haematologic and Biochemistry Values of High Altitude and Transhumant Pastoral Animals as a Reference for the Metabolic Studies - Barsila, Shanker Raj (Journal of Agriculture and Forestry University, 2025)
Transhumant grazing is a unique system of rearing domestic animals in the Himalayas. Migration to high elevations during summer is regarded as a strategy to increase energy intake, and it has been suggested that there is increased forage quality at high elevations. This led to the prediction that body weight is positively correlated with the proportion of high-altitude habitats. There are distinct physiological and metabolic changes in domestic animals during transhumance. Cold stress might further contribute to the physiological and metabolic differences at the same time as the low-altitude conditions of the animals. These changes have been further driven by genetic and nongenetic factors. This review provides few insights on such changes, which may help elucidate the scientific reasons behind the performance of sheep in the Himalayas. The physiological disposition of the animals to their nutrition could be monitored by hematology and serum biochemistry assays. Furthermore, changes in physiological states, such as the respiration rate and heart rate, are the simplest indirect measures of the stress tolerance of the animals during high-altitude grazing conditions, whereas blood metabolites can be observed as adaptive phenomena. Research reports on common physiological and metabolic traits and the reasons behind these changes under high-altitude conditions have been compiled in the present review.